INVESTIGASI EFEK INTERAKSI DARI KONSTRUK THEORY OF PLANNED BEHAVIOR (TPB) DALAM PENGGUNAAN TEKNOLOGI INFORMASI DI DINAS PROVINSI MALUKU - , Kamala Soleman ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Information systems studies largely ignore the effects of interaction. This study applies a theoretical model of planning behavior (TPB) to reveal the effect of the interaction between the theoretical constructs. Interaction in question is the interaction between attitude and subjective norm on intention of use of information technology. Interaction between attitude and facility conditions on intention of using information technology as well as the interaction between intentions and facility conditions the use of information technology. By revealing the structure of the interaction effects can clarify the cause and effect relationship constructs on behavioral use of information technology. Through a survey approach, the data obtained from 144 employees in finance and accounting Moluccas Provincial Departement. Testing hypotheses with predictive models in engineering analysis using Partial Least Square.